Graduation Reception CPA Graduates, Northeast Missouri State University, Kirksville, Mo., May 09, 1987 - Northeast Missouri State University (Kirksville, Mo.) (1987)
This graduation reception covers the CPA exam candidates on May 09, 1987 at the Northeast Missouri State University in Kirksville, MO